2009
DOI: 10.1194/jlr.m800620-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Depot-specific effects of the PPARγ agonist rosiglitazone on adipose tissue glucose uptake and metabolism

Abstract: We investigated mechanisms whereby peroxisome proliferator-activated receptor g (PPARg) agonism redistributes lipid from visceral (VF) toward subcutaneous fat (SF) by studying the impact of PPARg activation on VF and SF glucose uptake and metabolism, lipogenesis, and enzymes involved in triacylglycerol (TAG) synthesis. VF (retroperitoneal) and SF (inguinal) of rats treated or not for 7 days with rosiglitazone (15 mg/kg/day) were evaluated in vivo for glucose uptake and lipogenesis and in vitro for glucose meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 33 publications
5
57
0
3
Order By: Relevance
“…7C). Studies have reported differences between subcutaneous and visceral adipose tissues in function as well as in sensitivity to TZDs (25). These results were also consistent with those from lipodystrophy patients with TZDs treatment (26).…”
Section: Effects Of Thiazolidinedione Treatment Of Asko Micesupporting
confidence: 85%
“…7C). Studies have reported differences between subcutaneous and visceral adipose tissues in function as well as in sensitivity to TZDs (25). These results were also consistent with those from lipodystrophy patients with TZDs treatment (26).…”
Section: Effects Of Thiazolidinedione Treatment Of Asko Micesupporting
confidence: 85%
“…Because NFAT contributes to proinflammatory cytokine expression in adipocytes, the ability of lipin 1 to repress NFAT transcription may be important for regulating macrophage recruitment to the fat tissue. It should also be noted that the lipin 1 expression is increased by the thiazolidinedione (TZD) class of anti-diabetic drugs (11,58). This is intriguing since the TZDs improve insulin sensitivity and reduce inflammatory gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Triglyceride synthesis is facilitated by lipoprotein lipase (LPL)-mediated free fatty acid (FFA) uptake from (very) low-density lipoprotein and chylomicron and de novo lipogenesis via insulin-dependent glucose uptake by Glut4. Overall ∼10-15% of ingested glucose is transported into adipocytes (Kahn, 1996;Rosen and Spiegelman, 2006), of which ∼50% is used to synthesize glycerol and fatty acids (Festuccia et al, 2009). Interestingly, both LPL activity, especially in obese men (Boivin et al, 2007), and glucose uptake are higher in VAT than in SAT (Perrini et al, 2008;Veilleux et al, 2009;Virtanen et al, 2002), even though Glut 4 expression is lower (Lefebvre et al, 1998).…”
Section: Metabolic Risk Is Associated With Individual Adipose Tissue mentioning
confidence: 99%